Crossword Puzzle Strategy and Student Engagement Improve Learning Outcomes in Faith and Morality: Strategi Crossword Puzzle dan Keaktifan Siswa Meningkatkan Hasil Belajar Akidah Akhlak - Aina Nur Hilmy Harahap; Wahyudin Nur Nst; Mohammad Al Farabi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: In Islamic education, fostering both knowledge and character is central to achieving holistic learning outcomes. Specific Background: However, traditional teaching methods in subjects like Akidah Akhlak often fail to engage students effectively, resulting in low academic performance. Knowledge Gap: There is limited empirical evidence on the role of active learning strategies, such as crossword puzzles, in enhancing religious education outcomes, particularly when combined with student activeness. Aims: This study aims to investigate the effects of the crossword puzzle learning strategy and student activeness on the learning outcomes of Akidah Akhlak among fifth-grade students at MIN 3 Kota Medan. Results: Using a 2x2 factorial quasi-experimental design, findings from ANOVA revealed significant main effects of both the crossword puzzle strategy and student activeness, as well as their interaction, on learning outcomes. Novelty: This study introduces the integration of crossword puzzles—a typically secular and recreational activity—into religious education as an innovative pedagogical tool. Implications: The findings suggest that combining interactive strategies with increased student participation can significantly improve cognitive and affective learning in Akidah Akhlak, thereby offering a promising model for enhancing Islamic learning environments in primary education.Highlight : Crossword puzzle strategies have been proven to improve students' learning outcomes in Akidah Akhlak. Student activity significantly affects learning outcomes. There is an interaction between learning strategies and student activity on learning outcomes. Keywords : Crossword Puzzles, Student Activity, Learning Outcomes, Faith and Morals, Learning Strategies